The Effect of Service Quality and Facilities on Purchasing Decisions at UD. Bintang Petani Jaya in Pematangsiantar - Risma Munthe; Adat Muli Peranginangin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research is based on a casual relationship that is causal in nature, there are independent variables (variables that influence), dependent variables (variables that are affected) and mediating variables (variables that affect the relationship between the independent variable and the independent variable. Based on the results, it can be seen that the coefficient of determination (adjusted R2) is 0.403. This value means that the effect of the independent variable (service quality and facilities) on the dependent variable (purchase decision) is 40.3% while the remaining 59.7% is influenced by the other purchasing decision factors that are not examined. Based on the results of the F test, it is known that the significant level value obtained is 0,000 and it is smaller than the significant standard at the level of trust 5% or 0.05 and the comparison between F count and F table, where F counts are 15,507 is greater than F table which is 2,922, so it can be It is concluded that Ha is accepted or the quality of services and facilities has a significant effect on purchasing decisions.